2020
DOI: 10.1093/gerona/glaa212
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Changes Associated With Cardiac Aging Are Sex-Specific and Graded by Frailty and Inflammation in C57BL/6 Mice

Abstract: We investigated whether late-life changes in cardiac structure and function were related to high levels of frailty and inflammation in male and female mice. Frailty (frailty index), ventricular structure/function (echocardiography) and serum cytokines (multiplex immunoassay) were measured in 16 and 23-month-old mice. Left ventricular (LV) mass and septal wall thickness increased with age in both sexes. Ejection fraction increased with age in males (60.4±1.4 vs 68.9±1.8%; p<0.05) but not females (58.8±2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 57 publications
(56 reference statements)
1
8
0
Order By: Relevance
“…Recently, a study revealed increased mass and collagen level of the left ventricle, as well as the thickness of the septal wall in aged mice, associated with increased expressions of IL-1α, IL-6 and TNFα, suggesting that cardiac structural and functional changes with age are closely graded with frailty and inflammation markers [ 52 ]. NLRP3 inflammasome-related inflammaging has been activated with age in most body tissues and organs including heart [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a study revealed increased mass and collagen level of the left ventricle, as well as the thickness of the septal wall in aged mice, associated with increased expressions of IL-1α, IL-6 and TNFα, suggesting that cardiac structural and functional changes with age are closely graded with frailty and inflammation markers [ 52 ]. NLRP3 inflammasome-related inflammaging has been activated with age in most body tissues and organs including heart [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The induction of fibrosis and IL-1α and IL-6 inflammatory cytokines genes observed here were less remarkable in the NLRP3 −/− mice. Recently, interstitial and perivascular cardiac fibrosis was described in aged WT mice, with non-significant changes in aged NLRP3 −/− ones, where increased IL-6 serum and protein levels in the cardiac tissues of old WT and NLRP3 −/− mice were observed [ 48 ], and thus, the reduction of collagenous tissue infiltrations in the aged myocardium of NLRP3 −/− mice assured the attenuation of fibrosis upon NLRP3 depletion [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While inclusion of three age groups is novel and advances current literature which at most compares two, we would benefit from additional age groups-i.e., middle aged, as some studies suggest that cardiac function begins to change at around 12 months-both because of aging per se and between sexes [26]. Sex differences in age-related declines in cardiac function have been previously reported [48], with worse systolic function in male compared to female mice [49], suggesting a lifecourse comparison in males and females is warranted. The higher heterogeneity in female mice is significant and warrants discussion.…”
Section: Limitations and Conclusionmentioning
confidence: 96%
“…Mice were randomized by body weight and assigned to CON diet-fed group (n = 10) or CDAA diet fed group (n = 10) and were treated with anti-IL-1β Mab (n = 9) or isotype control (n = 10) for 8 weeks. Older male mice were used, due to their susceptibility to frailty and chronic inflammation-driven cardiac function decline 74 . The animals were treated two times per week with a dose of 50 µg/mouse 75 .…”
Section: Methodsmentioning
confidence: 99%